Fostering Early Childhood Attachment: The Impact of Caregiver Relationships in Islamic Boarding School Education - Rohmah, Lailatu; Sulong, Komareeyah (Al-Athfal: Jurnal Pendidikan Anak, 2023)
Purpose – This study aimed to explore the role of attachment in the educational context of early childhood students (santri) residing and learning in Pesantren Mambaul Hisan, Indonesia. The research sought to investigate the attachment dynamics between 5- and 6-year-old santri and their caregivers, including its impact on cognitive and socio-emotional development. Design/methods/approach – This research adopted a qualitative case study approach, employing in-depth interviews, participant observation, and careful document analysis. The sample was selected purposively and consisted of 24 early childhood santri, 2 Islamic boarding school leaders, and 5 caregivers. Data were analyzed to understand the role of secure attachment in attaining Islamic boarding school educational goals. Findings – The study revealed that secure attachment among early childhood santri fostered comfortable communication, enhanced cognitive development, and promoted socio-emotional growth. The secure attachment of these young students played a positive role in achieving the educational objectives of the pesantren. This research contributed to the existing knowledge on the psychology of early childhood santri, socio-emotional development, and attachment in an Islamic boarding school context, enriching our understanding of the role of passion in Islamic boarding school education. Research implications/limitations – The findings of this study have important implications for improving the quality of early childhood education in Islamic boarding school settings. It underscores the significance of fostering secure attachment and the potential benefits of implementing attachment-based strategies in the education of young santri.  Practical implications – Understanding the role of attachment in Islamic boarding school education for young children can inform the development of more effective educational strategies and support systems. Originality/value – This study adds a novel perspective by examining the role of attachment in the context of Islamic boarding school education for early childhood students. Paper type Research paper